2021
DOI: 10.1002/ece3.8292
|View full text |Cite
|
Sign up to set email alerts
|

Space‐for‐time is not necessarily a substitution when monitoring the distribution of pelagic fishes in the San Francisco Bay‐Delta

Abstract: Occupancy models are often used to analyze long-term monitoring data to better understand how and why species redistribute across dynamic landscapes while accounting for incomplete capture. However, this approach requires replicate detection/non-detection data at a sample unit and many long-term monitoring programs lack temporal replicate surveys. In such cases, it has been suggested that surveying subunits within a larger sample unit may be an efficient substitution (i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…Since the vast majority (78%) of the sampling days had the occupancy state observed in just one replicate sample, we surmise that the detection and misidentification model estimated much fewer samples as truly occupied (i.e., it treated many of these single observations as false-positive detections), which would result in a higher detection rate, particularly under the baseline condition. Further, we found that the detection of juvenile winter-run salmon occupancy was spatially dependent among sampling locations and negatively related to clearer water and higher mean river flow, which is consistent with other fish studies conducted in the Estuary (Perry et al 2016;Peterson and Barajas 2018;Duarte and Peterson 2021;Mahardja et al 2021). Therefore, our study demonstrates that the false-negative and false-positive error rates in the juvenile winter-run salmon count data used to inform DCC gate operation decisions are capable of biasing occupancy estimates and thereby distorting our understanding of the factors influencing juvenile winterrun salmon distribution.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Since the vast majority (78%) of the sampling days had the occupancy state observed in just one replicate sample, we surmise that the detection and misidentification model estimated much fewer samples as truly occupied (i.e., it treated many of these single observations as false-positive detections), which would result in a higher detection rate, particularly under the baseline condition. Further, we found that the detection of juvenile winter-run salmon occupancy was spatially dependent among sampling locations and negatively related to clearer water and higher mean river flow, which is consistent with other fish studies conducted in the Estuary (Perry et al 2016;Peterson and Barajas 2018;Duarte and Peterson 2021;Mahardja et al 2021). Therefore, our study demonstrates that the false-negative and false-positive error rates in the juvenile winter-run salmon count data used to inform DCC gate operation decisions are capable of biasing occupancy estimates and thereby distorting our understanding of the factors influencing juvenile winterrun salmon distribution.…”
Section: Discussionsupporting
confidence: 91%
“…Further, we found that the detection of juvenile winter‐run salmon occupancy was spatially dependent among sampling locations and negatively related to clearer water and higher mean river flow, which is consistent with other fish studies conducted in the Estuary (Perry et al. 2016; Peterson and Barajas 2018; Duarte and Peterson 2021; Mahardja et al. 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We assumed that repeated station‐level surveys within a hexagon were independent Bernoulli trials, and we considered individual stations and survey weeks to be replicate surveys (5 stations × 8 weeks = 40 survey occasions). This structure was chosen in order to incorporate conditions that influence detection at the level of individual ARU stations to ensure that their effects were accurately evaluated (e.g., Duarte & Peterson, 2021).…”
Section: Methodsmentioning
confidence: 99%